Positive and Negative Impacts of Poligamy in The Life of Muslim Family - Rohmadi, Rohmadi; Fauzan, Fauzan; Jafar, Wahyu Abdul (Madania: Jurnal Kajian Keislaman, 2022)
This study aims to reveal in detail the positive and negative impacts that arise from polygamy in Muslim family life. This research is a literature review, which uses documentation techniques in finding the required data. While the analytical method used is the inductive method. After conducting in-depth research, conclusions are obtained, including: The positive impact of polygamy is the opening of a way out of emergency conditions that occur in the household. Polygamy can be a solution for people to avoid committing adultery/ infidelity. Polygamy can also be a solution for someone to have children if his first wife is barren, protect widows, or channel the sexual needs of a husband who cannot be channeled properly with his first wife. While the negative impact that arises from polygamy for Muslim families is psychologically, a wife will feel disturbed and hurt to see her husband having sex with other women. A number of studies have shown that the average wife when she finds out her husband remarried spontaneously experiences feelings of depression, prolonged stress, sadness and disappointment. In addition, the relationship between husband and wife and their extended family is not harmonious. Marriage essentially connects the bond between two large families, polygamy makes the bond disrupted, maybe even broken. In addition, in the life of a polygamous family, of course, there are concerns in fostering and meeting family needs. : Penelitian ini bertujuan untuk mengungkap secara detail dampak positif dan negatif yang muncul dari poligami dalam kehidupan berkeluarga muslim. Penelitian ini bersifat kajian pustaka, yang mengunakan teknik dokumentasi dalam mencari data-data yang diperlukan. Sedangkan metode analisa yang digunakan adalah metode induktif. Setelah dilakukan penelitian secara mendalam maka diperoleh kesimpulan, antara lain: Dampak positif poligami adalah terbukanya jalan keluar dari kondisi darurat yang terjadi dalam rumah tangga. Poligami dapat menjadi solusi bagi orang terhindar dari berbuat zina/ perselingkuhan. Poligami juga bisa menjadi solusi bagi seseorang untuk memiliki keturunan jika istri pertamanya mandul, melindungi para janda, atau menyalurkan kebutuhan seks suami yang tidak dapat tersalurkan dengan baik dengan istri pertamanya. Sedangkan dampak negatif yang muncul dari poligami bagi keluarga muslim adalah secara psikologi, seorang isteri akan merasa terganggu dan sakit hati melihat suaminya berhubungan dengan perempuan lain. Sejumlah penelitian menunjukkan bahwa rata-rata isteri begitu mengetahui suaminya menikah lagi secara spontan mengalami perasaan depresi, stres berkepanjangan, sedih dan kecewa. Selain itu, hubungan suami isteri dan keluarga besarnya menjadi tidak harmonis. Perkawinan pada esensinya menyambung ikatan antara dua keluarga besar, poligami membuat ikatan itu terganggu, bahkan mungkin terputus. Selain itu, dalam kehidupan keluarga poligami tentunya terdapat kekhawatiran dalam membina dan memenuhi kebutuhan keluarga.